AroER Tri-Screen Is a Biologically Relevant Assay for Endocrine Disrupting Chemicals Modulating the Activity of Aromatase and/or the Estrogen Receptor - Chen, Shiuan (Oxford University Press, 2014)
Endocrine disrupting chemicals (EDCs) interfere with the biosynthesis, metabolism, and functions of steroid hormones, including estrogens and androgens. Aromatase enzyme converts androgen to estrogen. Thus, EDCs against aromatase significantly impact estrogen- and/or androgen-dependent functions, including the development of breast cancer. The current study aimed to develop a biologically relevant cell-based high-throughput screening assay to identify EDCs that act as aromatase inhibitors (AIs), estrogen receptor (ER) agonists, and/or ER antagonists. The AroER tri-screen assay was developed by stable transfection of ER-positive, aromatase-expressing MCF-7 breast cancer cells with an estrogen responsive element (ERE) driven luciferase reporter plasmid. The AroER tri-screen can identify: estrogenic EDCs, which increase luciferase signal without 17β-estradiol (E2); anti-estrogenic EDCs, which inhibit the E2-induced luciferase signal; and AI-like EDCs, which suppress a testosterone-induced luciferase signal. The assay was first optimized in a 96-well plate format and then miniaturized into a 1536-well plate format. The AroER tri-screen was demonstrated to be suitable for high-throughput screening in the 1536-well plate format, with a 6.9-fold signal-to-background ratio, a 5.4% coefficient of variation, and a screening window coefficient (Z-factor) of 0.78. The assay suggested that bisphenol A (BPA) functions mainly as an ER agonist. Results from screening the 446 drugs in the National Institutes of Health Clinical Collection revealed 106 compounds that modulated ER and/or aromatase activities. Among these, two AIs (bifonazole and oxiconazole) and one ER agonist (paroxetine) were confirmed through alternative aromatase and ER activity assays. These findings indicate that AroER tri-screen is a useful high-throughput screening system for identifying ER ligands and aromatase-inhibiting chemicals.